What is Necromedia? - O’Gorman, Marcel (Intermédialités / Intermediality, 2003)
This paper explores the collusion of death and technology by investigating: the military's early adoption of new technologies for the purpose of human destruction; superstition and ghost industries invoked by the mainstreaming of new technologies; the use of technology to push us into a posthuman era that heralds and celebrates the end of liberal humanism; technology's promise of immortality, which causes us to forget our finitude. The exploration is framed by various media scenes extracted from two recent Hollywood movies, Vanilla Sky (Crowe, 2001) and American Beauty (Mendes, 1999). The paper is not about these movies, but rather, it draws on them as case studies, information narratives about the incorporation of technology in American culture. By defining this new area of study and coining a new term, the author hopes to provoke interest in Necromedia Theory as an antidote to the uncritical incorporation of new technologies into everyday life, and to the relentless development of technology for technology's sake.